Nas asas do vapor: construção do espaço ferroviário em Pelotas/RS (fim do séc. XIX, início do séc. XX) - Schmitz, Maira Eveline (2013)
This work has a theme the railroad in the city of Pelotas, in the specific period of 1884, time of inauguration of the Rio Grande Bagé Railroad and railway station of Pelotas until the first decades of the 20th century, between the years 1910 and 1920. The central object of the research is the relationships and social conflicts that came with trains and exceeded the space station, building what can be called "urban railway area". The focus, therefore, is directed to visual development and to the formation of specific sociability at these spacialities. For the preparation of this work was to analyze, mainly, through newspapers and photographs that represent the area of the railroad in the period, added to reports and technical regulations, correspondence and memoirs. In relation to the methodology with the images, starting work as Ana Maria Mauad and Zita Possamai, the fonts was divided into thematic categories; after, following the contributions of Canabarro, we opted for a scheme of analysis that focuses on the different planes of an image, whether in relation to what is shown, or the way that evokes the representation; lastly, the line interpretive theoretical and methodological started the three main spots suggested by Ulpiano Bezerra de Menezes, to think about the relationship of the History with pictures: visual, the visible and the vision. In relation to the journals, followed the line of interpretive by Tania Regina de Luca. In a sense, the treatment of journals did not differ much from that given to images, being also classified by themes, to continue after an analysis centered on how the narratives were exposed and its content